Colorless semi-insulating silicon carbide crystal as well as preparation method and application thereof
By using boron powder for doping during the synthesis of silicon carbide crystals, the problem of difficulty in reducing the nitrogen content in artificially synthesized colorless moissumite is solved, and the preparation of high-yield and low-cost colorless semi-insulating silicon carbide crystals is achieved, and the colorless proportion of crystals is more than 90%.
Patent Information
- Application Number
- CN202510055313.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-11
AI Technical Summary
When the prior art synthesizes colorless moissanite, it is difficult to effectively reduce the nitrogen content, resulting in abnormal crystal color, affecting the refractive effect of fire color, and is costly and poorly practical.
By mixing carbon powder, silicon powder and boron powder and vacuum heat treatment, a dopant precursor was obtained, and then sintered to obtain a dopant, which was mixed with silicon carbide to be treated, and crystal growth was performed to obtain a colorless semi-insulating silicon carbide crystal.
The yield of colorless semi-insulating silicon carbide crystals is greatly improved, the nitrogen removal step is avoided, the cost is significantly reduced, and the prepared crystals are highly repetitive, with colorless accounting for more than 90%.
Smart Images

Figure CN119800491A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon carbide crystals and relates to a colorless semi-insulating silicon carbide crystal and a preparation method and application thereof. Background Art
[0002] Moissanite (also known as moissanite diamond), natural ore is mainly dark green and black, and the number is very rare. Most of the moissanite circulating in the market is artificially synthesized. Its chemical name is SiC. It looks very similar to diamond. Its Mohs hardness is second only to diamond, and it has a diamond luster. After careful polishing, it can show a very high gloss. The refractive index of moissanite is no≈2.648 and ne≈2.691, which is higher than that of diamond. It has a strong refractive ability, which can make light refract and reflect multiple times inside the gemstone, thus producing dazzling fire. The dispersion value of moissanite is 0.104, which is much higher than the 0.044 of diamond. Therefore, the fire of moissanite is more brilliant than diamond, and it is very popular in the market. At the same time, according to different doping and treatment methods, moissanite (silicon carbide) can have semi-insulating properties.
[0003] Pure moissanite is usually colorless and transparent, but it is difficult to reduce the nitrogen in the growth system to 10 during the artificial synthesis process. 16 The usual practice is to use insulation felt and graphite materials with ash content ≤5ppm, gas with purity>6N, high-purity silicon carbide raw materials, repeated calcination of raw and auxiliary materials, etc., which greatly increases the cost and reduces production efficiency. Despite this, the yield of artificial synthesis is still not high, mainly reflected in the excessive nitrogen in the system, which leads to abnormal crystal color, such as blue, brown, brown, blue-gray, etc., affecting the refraction effect of fire and poor appreciation.
[0004] CN118639319A discloses a method for manufacturing colorless moissanite with high efficiency and high productivity, the method comprising the following steps: (S.1) cutting semi-insulating seed crystals to obtain seed crystals with regular shapes; (S.2) coating glue on the surface of the seed crystals with regular shapes and arranging and splicing them to obtain large-sized spliced seed crystals; (S.3) bonding the large-sized spliced seed crystals to the surface of a flexible substrate, and then coating glue on the other side of the flexible substrate; (S.4) bonding the flexible substrate together with the large-sized spliced seed crystals to a physical vapor deposition device, and depositing silicon carbide crystals on the surface of the large-sized spliced seed crystals by physical vapor deposition, thereby forming colorless moissanite.
[0005] CN109911899A discloses a method for preparing colorless moissanite, comprising: placing a high-purity semi-insulating silicon carbide wafer into a crucible, loading a furnace and setting growth parameters, heating the crucible, sublimating the high-purity semi-insulating wafer and recrystallizing it at the top of the crucible, cooling the crucible and taking it out of the furnace to obtain colorless moissanite. The growth parameters are: temperature at 2000-2300°C and pressure at 1-700 Torr.
[0006] Although the method described in the above scheme obtains colorless moissanite, it has extremely high requirements on the raw materials used, resulting in high cost and poor practicality. Summary of the invention
[0007] The purpose of the present invention is to provide a colorless semi-insulating silicon carbide crystal and a preparation method and application thereof. The present invention prepares a colorless semi-insulating silicon carbide crystal, which not only greatly improves the yield of the colorless semi-insulating silicon carbide crystal, but also does not require nitrogen removal, avoids the nitrogen removal step, and greatly reduces the cost.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a colorless semi-insulating silicon carbide crystal, the preparation method comprising the following steps:
[0010] (1) mixing carbon powder, silicon powder and boron powder to obtain a mixed material, and performing vacuum heat treatment on the mixed material to obtain a dopant precursor;
[0011] (2) sintering the dopant precursor to obtain the dopant, and detecting the content of the boron element in the dopant;
[0012] (3) taking the first silicon carbide to be treated to test its boron and nitrogen content, calculating the required amount of dopant according to the boron and nitrogen content in the first silicon carbide to be treated and the dopant, and mixing the first silicon carbide to be treated with the dopant to obtain a mixture, placing the mixture in a doping zone of a heating device, adding the second silicon carbide to be treated, the second silicon carbide to be treated completely covers the mixture, and performing crystal growth to obtain the colorless semi-insulating silicon carbide crystal;
[0013] Wherein, in the mixture described in step (3), the molar ratio of boron element to nitrogen element is (0.99-1.01):1.
[0014] The first silicon carbide to be processed and the second silicon carbide to be processed in the present invention are of exactly the same type, i.e., colored silicon carbide containing elements such as nitrogen and boron. The first and the second are only used for distinction. The present invention does not limit the forms of the two, which can be either silicon carbide crystals or silicon carbide powder.
[0015] The present invention prepares a boron-containing silicon carbide dopant precursor in advance. Since the boron atom has one less electron than the silicon atom, after the boron element is doped, an electron defect energy level is formed in the crystal, and a new electron state is introduced into the forbidden band of silicon carbide. When light is irradiated onto the silicon carbide crystal, the electrons in the crystal absorb photons of specific energy, and the electrons can more easily transition from the ground state to these defect energy levels, or from the defect energy levels to higher energy levels. The energy of the photons absorbed during this electronic transition process changes, so that the absorption and reflection characteristics of moissanite to light of different wavelengths also change, thereby showing a change in color on a macro scale. When the content of the doped boron atoms is close to the content of the nitrogen atoms in the crystal (that is, the molar ratio of the boron element to the nitrogen element is (0.99-1.01):1), the crystal can be colorless.
[0016] Preferably, the mass ratio of the carbon powder, silicon powder and boron powder in step (1) is 7:3:(0.0001-0.005), for example: 7:3:0.0001, 7:3:0.0005, 7:3:0.001, 7:3:0.002 or 7:3:0.005, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the median particle size D50 of the carbon powder in step (1) is 20 μm to 50 μm, for example, 20 μm, 25 μm, 30 μm, 40 μm or 50 μm, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0018] Preferably, the median particle size D50 of the silicon powder in step (1) is 400 μm to 600 μm, for example, 40 μm, 45 μm, 50 μm, 55 μm or 60 μm.
[0019] Preferably, the purity of the boron powder in step (1) is >5N.
[0020] Preferably, the particle size of the boron powder in step (1) is 0.001 μm to 1 μm, for example, 0.001 μm, 0.003 μm, 0.05 μm, 0.2 μm or 1 μm, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0021] Preferably, the pressure of the vacuum heat treatment in step (1) is less than 10 -3 Pa.
[0022] Preferably, during the vacuum heat treatment in step (1), heating is performed using an induction coil and / or a resistor.
[0023] Preferably, the temperature of the vacuum heat treatment in step (1) is 1000°C to 1200°C, for example, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, the vacuum heat treatment time in step (1) is 1 h to 15 h, for example, 1 h, 5 h, 8 h, 10 h or 15 h, etc., preferably 8 h to 12 h.
[0025] Preferably, the atmosphere of the sintering treatment in step (2) includes a protective atmosphere.
[0026] Preferably, the protective atmosphere comprises nitrogen and / or argon.
[0027] Preferably, the pressure of the sintering treatment in step (2) is 5 mbar to 100 mbar, for example, 5 mbar, 8 mbar, 10 mbar, 20 mbar, 50 mbar or 100 mbar, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0028] Preferably, the heating rate of the sintering treatment in step (2) is 0.5°C / min to 5°C / min, for example: 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the temperature of the sintering treatment in step (2) is 1600°C to 1900°C, for example, 1600°C, 1680°C, 1700°C, 1800°C or 1900°C, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the holding time of the sintering treatment in step (2) is 3 h to 15 h, for example, 3 h, 5 h, 8 h, 10 h, 12 h or 15 h, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0031] Preferably, after the sintering treatment in step (2), a protective gas is introduced to a system pressure of 50 kPa to 80 kPa, for example, 50 kPa, 55 kPa, 60 kPa, 70 kPa, 75 kPa or 80 kPa, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable, and cooling is performed.
[0032] Preferably, the median particle size D50 of the dopant in step (2) is 10 μm to 100 μm, for example, 10 μm, 20 μm, 50 μm, 80 μm or 100 μm, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0033] Preferably, the method for detecting the content of boron in the dopant in step (2) comprises secondary ion mass spectrometry (SIMS) detection.
[0034] Preferably, in step (3), the mass of the first silicon carbide to be treated is 500g to 5000g, for example, 500g, 800g, 1000g, 2000g or 5000g, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, taking the area of the heating device as 100%, the area of the doping region is 40% to 90%, for example 40%, 50%, 60%, 80% or 90%, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the heating device comprises a crucible.
[0037] Preferably, taking the height of the heating device as 100%, the height of the mixed material in the doping zone is 50% to 80%, for example, 50%, 55%, 60%, 70%, 80% or 90%, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the temperature of the crystal growth in step (3) is 2100°C to 2300°C, for example, 2100°C, 2150°C, 2200°C, 2250°C or 2300°C.
[0039] Preferably, the pressure of the crystal growth in step (3) is 0.5 mbar to 5 mbar, for example, 0.5 mbar, 1 mbar, 2 mbar, 3 mbar, 4 mbar or 5 mbar.
[0040] Preferably, a protective gas is introduced during the crystal growth process in step (3).
[0041] Preferably, the protective gas comprises nitrogen and / or argon.
[0042] Preferably, the flow rate of the protective gas is 100 sccm to 1000 sccm, for example, 100 sccm, 200 sccm, 500 sccm, 800 sccm or 1000 sccm.
[0043] Preferably, the growth time of the crystal growth in step (3) is 50 h to 100 h, for example: 50 h, 60 h, 70 h, 80 h, 90 h or 100 h, etc.
[0044] In a second aspect, the present invention provides a colorless semi-insulating silicon carbide crystal, which is prepared by the preparation method described in the first aspect.
[0045] In a third aspect, the present invention provides an application of the colorless semi-insulating silicon carbide crystal as described in the second aspect, wherein the colorless semi-insulating silicon carbide crystal is used for jewelry, communications or optoelectronic devices.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] (1) The present invention prepares a colorless semi-insulating silicon carbide crystal, which not only greatly improves the yield of the colorless semi-insulating silicon carbide crystal, but also does not require nitrogen removal, avoids the nitrogen removal step, and greatly reduces the cost.
[0048] (2) The colorless semi-insulating silicon carbide crystals prepared by the present invention have high repeatability, and the colorless proportion accounts for more than 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a schematic diagram of the loading position provided in step (3) of an embodiment of the present invention, wherein 1 is the doping area, 2 is the non-doping area, and 3 is the crucible. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0051] The purity of the single substance powder used in the examples of the present invention and the comparative examples is >5N.
[0052] Example 1
[0053] This embodiment provides a colorless semi-insulating silicon carbide crystal, which is prepared by the following method:
[0054] (1) Silicon powder with a median particle size D50 of 500 μm, carbon powder with a median particle size D50 of 30 μm, and boron powder with a particle size of 0.01 μm to 1 μm were mixed in a graphite crucible at a mass ratio of 7:3:0.001, and then the mixture was placed in a furnace and vacuumed to a pressure of <10 -3 Pa, turn on the heating power supply and raise the temperature to 1100°C for vacuum heat treatment for 10 hours to obtain a dopant precursor;
[0055] (2) Argon gas was injected into the furnace, and the pressure in the furnace was controlled to be 15 mbar. The temperature was raised to 1700°C at a heating rate of 1.5°C / min. After sintering for 6 hours, the heat source was turned off and argon gas was injected to a pressure of 80 kPa. After cooling to room temperature, the dopant with a particle size of 80 μm to 100 μm was taken out. The boron concentration in the dopant was 1.50×10 19 / cm 3 ;
[0056] (3) Take the light blue silicon carbide crystal, cut it longitudinally, and detect the boron content by SIMS. The content is 9.42×10 15 / cm 3 , Nitrogen concentration 2.50×10 16 / cm 3 , the light blue silicon carbide crystals were mixed with 2.91 g of dopant according to the molar ratio of boron to nitrogen being 1:1 to obtain 1400 g of doping material, and the doping material was mixed with the silicon carbide to be treated according to the following method: Figure 1 The doping material is loaded at the position shown, the doping material is placed in the doping area 1 of the crucible 3, and the light blue silicon carbide crystal is placed in the non-doping area 2, completely covering the doping material, the doping area area is 75% of the crucible area, and the material height of the doping area is 65% of the crucible height. The growth temperature is 2200°C, the growth pressure is 1.5mbar, and the growth flow rate is 200sccm. The growth is carried out for 70 hours to obtain the colorless semi-insulating silicon carbide crystal. The silicon carbide powder used in this embodiment and the subsequent embodiments is selected from the same batch of materials, and the content of B element and N element is close.
[0057] Example 2
[0058] This embodiment provides a colorless semi-insulating silicon carbide crystal, which is prepared by the following method:
[0059] (1) Silicon powder with a median particle size D50 of 200 μm, carbon powder with a median particle size D50 of 20 μm, and boron powder with a particle size of 0.01 μm to 1 μm were mixed in a graphite crucible at a mass ratio of 7:3:0.005, and the mixture was placed in a furnace and evacuated to a pressure of <10 -3 Pa, turn on the heating power supply and raise the temperature to 1000°C for vacuum heat treatment for 10 hours to obtain a dopant precursor;
[0060] (2) Argon gas was injected into the furnace, and the pressure in the furnace was controlled to be 5 mbar. The temperature was raised to 1900°C at a heating rate of 5°C / min. After sintering for 3 hours, the heat source was turned off and argon gas was injected to a pressure of 50 kPa. After cooling to room temperature, the dopant with a particle size of 140 μm to 160 μm was obtained. The B concentration in the dopant was 8.1×10 19 / cm 3 ;
[0061] (3) Take a light brown silicon carbide crystal and cut it longitudinally. The boron content is 6.30×10 15 / cm 3 , nitrogen concentration 3.83×10 16 / cm 3 , light brown silicon carbide crystals were mixed with 1.11 g of dopant in a molar ratio of boron to nitrogen of 1:1 to obtain 900 g of doping material, and the doping material was mixed with the silicon carbide to be treated as follows Figure 1 The material is loaded at the position shown, the doping material is placed in the doping zone 1 of the crucible 3, and the light brown silicon carbide crystal is placed in the non-doping zone 2 to completely cover the doping material. The area of the doping zone is 40% of the area of the crucible, and the material height of the doping zone is 80% of the height of the crucible. The growth is carried out for 80 hours under the conditions of a growth temperature of 2250°C, a growth pressure of 2 mbar, and a growth flow rate of 200 sccm to obtain the colorless semi-insulating silicon carbide crystal.
[0062] Example 3
[0063] This embodiment provides a colorless semi-insulating silicon carbide crystal, which is prepared by the following method:
[0064] (1) Silicon powder with a median particle size D50 of 1000 μm, carbon powder with a median particle size D50 of 50 μm, and boron powder with a particle size of 0.01 μm to 1 μm were mixed in a graphite crucible at a mass ratio of 7:3:0.0001, and then the furnace was loaded and evacuated to a pressure of <10 -3 Pa, turn on the heating power supply and raise the temperature to 1200°C for vacuum heat treatment for 4 hours to obtain a dopant precursor;
[0065] (2) Argon gas was introduced into the furnace, the pressure in the furnace was controlled to be 100 mbar, and the temperature was raised to 1600°C at a heating rate of 0.5°C / min. After sintering for 15 hours, the heat source was turned off and nitrogen gas was filled to a pressure of 80 kPa. After cooling to room temperature, the dopant with a particle size of 70 μm to 100 μm was taken out. The boron concentration in the dopant was 1.95×10 18 / cm 3 ;
[0066] (3) Take the light blue silicon carbide crystal, cut it longitudinally, and detect the boron content by SIMS. 16 / cm 3 , Nitrogen concentration 4.50×10 16 / cm 3 According to the molar ratio of boron to nitrogen being 1:1, the light blue silicon carbide crystals were mixed with 12.21 g of dopant to obtain 2000 g of doping material, and the doping material was mixed with the silicon carbide to be treated as follows: Figure 1 The material is loaded at the position shown, the doping material is placed in the doping zone 1 of the crucible 3, and the light blue silicon carbide crystal is placed in the non-doping zone 2 to completely cover the doping material. The area of the doping zone is 90% of the area of the crucible, and the material height of the doping zone is 50% of the height of the crucible. The growth is carried out for 70 hours under the conditions of a growth temperature of 2200°C, a growth pressure of 1.5 mbar, and a growth flow rate of 200 sccm to obtain the colorless semi-insulating silicon carbide crystal.
[0067] Example 4
[0068] The only difference between this embodiment and the first embodiment is that the area of the doping region and the height of the material in the doping region are 100% of the crucible, and the other conditions and parameters are exactly the same as those in the first embodiment.
[0069] Example 5
[0070] The only difference between this embodiment and embodiment 1 is that the area of the doping region is 10% of the area of the crucible, the material height of the doping region is 5% of the height of the crucible, and other conditions and parameters are exactly the same as those in embodiment 1.
[0071] Example 6
[0072] The only difference between this embodiment and embodiment 1 is that the sintering temperature is 800° C., and the other conditions and parameters are exactly the same as those in embodiment 1.
[0073] Example 7
[0074] The only difference between this embodiment and embodiment 1 is that the sintering temperature is 2000° C., and the other conditions and parameters are exactly the same as those in embodiment 1.
[0075] Comparative Example 1
[0076] This comparative example uses the light blue silicon carbide crystal as described in Example 1, and replaces the dopant with boron powder according to the element ratio. Other conditions and parameters are exactly the same as those in Example 1.
[0077] Comparative Example 2
[0078] The only difference between this comparative example and Example 1 is that step (1) does not perform vacuum heat treatment, and the other conditions and parameters are exactly the same as those in Example 1.
[0079] Comparative Example 3
[0080] The only difference between this comparative example and Example 1 is that the light blue silicon carbide crystals are mixed with the dopant at a molar ratio of boron element to nitrogen element of 0.96:1 to obtain the doping material, and the other conditions and parameters are exactly the same as those in Example 1.
[0081] Comparative Example 4
[0082] The only difference between this comparative example and Example 1 is that the light blue silicon carbide crystals are mixed with the dopant at a molar ratio of boron element to nitrogen element of 1.03:1 to obtain the doping material, and the other conditions and parameters are exactly the same as those in Example 1.
[0083] Performance Testing:
[0084] Three crystals were grown in each group, and the percentage of colorless areas was observed under a special light for jade identification. The test results are shown in Table 1:
[0085] Table 1
[0086]
[0087]
[0088] As can be seen from Table 1, colorless crystals appeared in each of the embodiments of the present invention from Examples 1 to 8, and the proportion of colorless crystals in Examples 1 to 3 was > 90%, indicating that the present invention can greatly improve the yield of colorless semi-insulating silicon carbide crystals.
[0089] By comparing Example 1 with Examples 4-5, it can be seen that during the preparation process of the colorless semi-insulating silicon carbide crystals described in the present invention, the doping area has a significant effect on the color stratification of the colorless crystals. Since the powder at the edge and bottom of the crucible sublimates preferentially, too large an area of the doping area or too small a doping height will lead to uneven sublimation of the dopant, which will cause stratification of the color of the crystal in the early and later stages, reducing the yield of the colorless crystals.
[0090] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the colorless semi-insulating silicon carbide crystals of the present invention, the temperature of the sintering treatment will affect the performance of the dopant and thus affect the effect of obtaining the colorless semi-insulating silicon carbide crystals. The sintering treatment temperature is controlled at 1600°C to 1900°C, and the effect of obtaining the colorless semi-insulating silicon carbide crystals is better. If the sintering treatment temperature is too low, the boron powder cannot be incorporated into the silicon carbide through reaction, and the incorporated dopant still exists in a single substance form, volatilizes prematurely during the crystal growth and heating process, and cannot effectively enter the crystal, thereby contributing very little to the colorless crystal output. If the sintering treatment temperature is too high, on the one hand, the particle size of the prepared dopant will be larger, and the uniformity of the dopant distribution will be relatively poor when mixed with the silicon carbide powder. On the other hand, the prepared doped surface will also sublimate at high temperature, resulting in a difference in the boron content on the surface and inside of the dopant particle. After the silicon carbide powder is added, local boron excess or deficiency is likely to occur during the crystal growth process, and the color is prone to stratification.
[0091] By comparing Example 1 and Comparative Example 1, it can be seen that if boron powder is directly added, the weight of the boron powder is extremely low by calculation, and it is difficult to mix it evenly when directly added to silicon carbide powder. In addition, the boron powder exists in a single substance form and volatilizes prematurely during the crystal growth heating process, resulting in severe color stratification of the crystal.
[0092] From the comparison between Example 1 and Comparative Example 2, it can be seen that there is still a lot of nitrogen residue inside the dopant precursor prepared after the vacuum heat treatment is cancelled, resulting in incomplete improvement of the light blue area of the crystal.
[0093] By comparing Example 1 and Comparative Examples 3-4, it can be seen that when too little boron is doped, the light blue area of the crystal becomes lighter in color, but has not yet turned colorless. When excessive boron is doped, the absorption and reflection of light by the excessive boron changes, resulting in a light yellow layer in the initial color of the crystal.
[0094] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing colorless semi-insulating silicon carbide crystals, characterized in that: The preparation method comprises the following steps: (1) mixing carbon powder, silicon powder and boron powder to obtain a mixed material, and performing vacuum heat treatment on the mixed material to obtain a dopant precursor; (2) sintering the dopant precursor to obtain the dopant, and detecting the content of the boron element in the dopant; (3) taking the first silicon carbide to be treated to test its boron and nitrogen content, calculating the required amount of dopant according to the boron and nitrogen content in the first silicon carbide to be treated and the dopant, and mixing the first silicon carbide to be treated with the dopant to obtain a mixture, placing the mixture in a doping zone of a heating device, adding the second silicon carbide to be treated, the second silicon carbide to be treated completely covers the mixture, and performing crystal growth to obtain the colorless semi-insulating silicon carbide crystal; Wherein, in the mixture described in step (3), the molar ratio of boron element to nitrogen element is (0.99-1.01):
1.
2. The preparation method according to claim 1, characterized in that The mass ratio of carbon powder, silicon powder and boron powder in step (1) is 7:3:(0.0001-0.005); Preferably, the median particle size D50 of the carbon powder in step (1) is 20 μm to 50 μm; Preferably, the median particle size D50 of the silicon powder in step (1) is 400 μm to 600 μm; Preferably, the purity of the boron powder in step (1) is >5N; Preferably, the particle size of the boron powder in step (1) is 0.001 μm to 1 μm.
3. The preparation method according to claim 1 or 2, characterized in that: The pressure of the vacuum heat treatment in step (1) is less than 10 - 3 Pa; Preferably, during the vacuum heat treatment in step (1), heating is performed using an induction coil and / or a resistor; Preferably, the temperature of the vacuum heat treatment in step (1) is 1000° C. to 1200° C.; Preferably, the vacuum heat treatment time in step (1) is 1 h to 15 h, preferably 8 h to 12 h.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The atmosphere of the sintering treatment in step (2) includes a protective atmosphere; Preferably, the protective atmosphere comprises nitrogen and / or argon; Preferably, the pressure of the sintering treatment in step (2) is 5 mbar to 100 mbar; Preferably, the heating rate of the sintering treatment in step (2) is 0.5°C / min to 5°C / min; Preferably, the sintering temperature in step (2) is 1600° C. to 1900° C.; Preferably, the holding time of the sintering treatment in step (2) is 3 h to 15 h.
5. The preparation method according to any one of claims 1 to 4, characterized in that: After the sintering treatment in step (2), a protective gas is introduced until the system pressure reaches 50 kPa to 80 kPa, and then cooling is performed.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The median particle size D50 of the dopant in step (2) is 10 μm to 100 μm; Preferably, the method for detecting the content of boron in the dopant in step (2) comprises SIMS detection.
7. The preparation method according to any one of claims 1 to 6, characterized in that: Step (3) The mass of the first silicon carbide to be processed is 500 g to 5000 g; Preferably, the area of the doping region is 40% to 90% based on the area of the heating device being 100%; Preferably, taking the height of the heating device as 100%, the height of the mixed material in the doping region is 50% to 80%.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The temperature of the crystal growth in step (3) is 2100° C. to 2300° C.; Preferably, the pressure of the crystal growth in step (3) is 0.5 mbar to 5 mbar; Preferably, a protective gas is introduced during the crystal growth process in step (3); Preferably, the flow rate of the protective gas is 100 sccm to 1000 sccm; Preferably, the growth time of the crystal growth in step (3) is 50 h to 100 h.
9. A colorless semi-insulating silicon carbide crystal, characterized in that: The colorless semi-insulating silicon carbide crystal is obtained by the preparation method according to any one of claims 1 to 8.
10. An application of the colorless semi-insulating silicon carbide crystal as claimed in claim 9, characterized in that: The colorless semi-insulating silicon carbide crystal is used for jewelry, communications or optoelectronic devices.
Citation Information
Patent Citations
Preparation method of colorless moissanite
CN109911899A